If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 * 9 = w Multiply 4 * 9 36 = w Solving 36 = w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-1w' to each side of the equation. 36 + -1w = w + -1w Combine like terms: w + -1w = 0 36 + -1w = 0 Add '-36' to each side of the equation. 36 + -36 + -1w = 0 + -36 Combine like terms: 36 + -36 = 0 0 + -1w = 0 + -36 -1w = 0 + -36 Combine like terms: 0 + -36 = -36 -1w = -36 Divide each side by '-1'. w = 36 Simplifying w = 36
| 3x^2-4=-8x | | -5a^6(-7a^6-14)=0 | | 3x+6+6x=96 | | (3/10)x=1 | | 15.60=20(0.17w+0.44) | | 7x-54x=2x-4 | | (x-2/7)-(x+3/9)=1/11 | | 0.9Q^2-2Q+100=0 | | 15.60=20(x*0.17+0.44) | | 1/2x+12=5/6 | | b+-14=25 | | -3x-8+2x=13 | | 12=-4x-3x-9 | | (-5x^3+4)-(-8x^3)=0 | | 3x-4=-8x | | 15.60=20(0.17*19+0.44) | | (13z^8+10)-2z^8=0 | | 3(z-5)+8=17 | | -5x+1+3x=-3 | | 15.60=20(x+0.17)+0.44 | | 7x+4/2-6=3x/4 | | 3x-7+5x=-71 | | (5x-4)(9x+6)=0 | | -6/7x=41/3 | | 5/6x+1/2=9 | | 3(n-4)=48 | | 4s^2-4s-1=0 | | 4x*5.5-4x=12x | | 2+6x-7x=0 | | 7/3x-8/3=-9 | | 5/-5=15 | | -8+6f=5 |